Libyan EFL Teachers’ Perceptions about the Implementation of Communicative Language Teaching at a Secondary School in Libya (مجلة البحوث الأكاديمية, 2023)
This study focuses on the challenges that EFL Libyan teachers face in using Communicative Language Teaching (CLT). The aims of this study are to explore the problems that hinder the successful implementation of CLT at a secondary school and to find out the reasons behind these challenges. This paper is concerned with answering the research question: What are the main challenges that EFL Libyan teachers face in implementing CLT at a secondary school in Libya? It is qualitative study to explore EFL Libyan teachers perceptions and perspectives about CLT. Semi-structured interviews and observations in a number of taught sessions are used to generate data. This study forms a case study because it focuses on 10 participants who are selected purposively. The data are analysed manually by using thematic analysis. The findings of this study reveal that the major challenges are lack of sufficient knowledge of CLT, limitation of time for syllabus coverage, and large number of students. Moreover, the results show that the Libyan culture with regard to interaction of mixed genders has partially prevented teachers from applying certain activities that are crucial. Unfamiliarity with technology and insufficient technological resources are also perceived as challenges that have adversely affected the use of CLT activities. The results also indicate that the inspectors’ evaluation of teachers which is based on the use of the traditional methods of teaching is the biggest obstacle that prevents the adoption of CLT. This research has the potential to provide implications for the practitioners and the language policy makers for the improvement of the CLT practices in the Libyan context.